Congenital sub-mitral aneurysm: Anesthetics and surgical management - Jitendra V Kalbande; Subrata S Singha; Narendra Bodhey; Preetam Sahani (Annals of Cardiac Anaesthesia, 2024)
A sub-mitral left ventricular aneurysm is a rare condition. It is a congenital outpouching of the left ventricular wall, invariably occurring adjacent to the posterior mitral leaflet. Sub-mitral aneurysm (SMA) has usually been reported as a consequence of myocardial ischemia (MI), rheumatic heart disease, tuberculosis, and infective endocarditis. Nevertheless, there have been few case reports of congenital SMA in India. It usually presents with symptoms of heart failure. We report a rare case of congenital SMA in a 27-year-old young Indian and its successful management through a trans-aneurysmal approach.